Coated high-nickel material as well as preparation method and application thereof
By wrapping the NASICON type fast ion conductor and metal boride mixed layer on the high nickel material, the problem of structural instability and reaction with the electrolyte at high voltage is solved, and efficient lithium ion and electron transport, good heat dissipation and electrochemical stability are achieved.
Patent Information
- Application Number
- CN202510186675.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The structure of high nickel materials is unstable during charging, especially at high voltages, which easily leads to heat loss due to oxygen evolution, and easily reacts with the electrolyte to lead to gas production and performance of the battery.
The enclosure layer composed of a mixture of NASICON type fast ion conductor and metal boride is wrapped with high nickel material. The lithium ion transmission performance and electrochemical stability are improved through NASICON type fast ion conductors, and metal borides improve electronic conductivity and thermal conductivity.
It realizes high-nickel coating material with high surface ion/electronic conductivity, easy heat dissipation and good compatibility with electrolyte, improves charging and discharging efficiency, energy utilization and thermal stability, and extends the cycle life of the battery.
Smart Images

Figure CN119674046A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of positive electrode materials for lithium ion batteries, and relates to a coated high-nickel material and a preparation method and application thereof. Background Art
[0002] As global warming and environmental problems become increasingly severe, the world has proposed the development of clean energy generation, such as solar energy, wind energy, and hydrogen energy to replace traditional fossil energy generation. At the same time, in the field of transportation, it has also proposed the need to vigorously develop new energy vehicles to replace traditional fuel vehicles. Whether it is the development of clean energy generation or the development of new energy vehicles, it is necessary to develop high-performance energy storage batteries.
[0003] However, during the charging process, especially under high charging voltage, high-nickel materials are structurally unstable and prone to oxygen evolution, causing thermal runaway. At the same time, during the charging process, high-nickel materials are prone to react with the electrolyte, causing battery gas production and a decrease in battery performance.
[0004] The invention patent application with publication number CN115425214A discloses a coated modified high-nickel ternary positive electrode material, its preparation method and application. The preparation method comprises dispersing a phosphorus source, an aluminum source, a lithium source, a titanium source and an additive in a first solvent in sequence, obtaining a coated suspension for a first ball milling, obtaining a coated slurry for a first drying, obtaining a lithium titanium aluminum phosphate precursor, mixing the high-nickel ternary positive electrode material after the second ball milling and the second solvent and performing a third ball milling, obtaining a mixed slurry, and performing a second drying and sintering in sequence to obtain a coated modified high-nickel ternary positive electrode material; wherein the additive is B2O3 and / or SiO2. The invention patent application coats a layer of lithium titanium aluminum phosphate on the surface of the high-nickel ternary positive electrode material, which can increase the diffusion rate of lithium ions during charging and discharging, and effectively reduce the erosion of the electrolyte on the main body of the positive electrode material, thereby reducing the battery impedance, improving the residual alkali and electrochemical properties on the surface of the material, improving the cycle stability of the positive electrode material, and alleviating the thermal stability of the high-nickel positive electrode material.
[0005] The invention patent application with publication number CN116799291A discloses a NASICON type solid electrolyte, a positive electrode material, a preparation method and application thereof. The chemical structure of the NASICON type solid electrolyte is Li 1+x M 1 xT 2-x (PO4) y (M 2 O4) z, wherein 0≤x≤0.6, 1.5≤z≤4.5, 50%≤z / (y+z)≤100%; M1 includes at least one of Al, Y, Fe, Cr, Nb, and Zr; M2 includes at least one of V, Mo, W, and Nb. By introducing transition metal elements and limiting the proportion of transition metal elements, the electronic conductivity of the solid electrolyte is maximized, so that the solid electrolyte has the dual conduction properties of lithium ion conduction and electronic conduction. The NASICON type with the electronic-ion dual conduction property described in the invention patent is used as the coating material to form a modified ternary lithium-ion battery positive electrode material.
[0006] The invention patent application with publication number CN117199308A discloses wrapping layers on both sides of the positive electrode material, wherein the first wrapping layer is a fast ion conductor wrapping layer, and the second wrapping layer is a boride wrapping layer. The patent application utilizes the chemical inertness of the first wrapping layer to reduce the contact of the electrolyte with the positive electrode material and improve the transmission efficiency of lithium ions during the charging and discharging process, and utilizes the mechanical properties of the second wrapping layer to effectively prevent the electrolyte from corroding the positive electrode material, while suppressing the stress and strain of the positive electrode material during the lithium ion deintercalation process and alleviating the generation of microcracks. At the same time, the conductive properties of the boride are utilized to form a stable wrapping layer. However, the function of the first and second wrapping layers mentioned in the patent application is mainly to prevent the electrolyte from corroding the positive electrode material, and there is no mention of how to dissipate the heat generated by the positive electrode material.
[0007] Although the above patent can improve the structural stability of the material under high voltage and the interface stability with the electrolyte to a certain extent through surface coating, and can promote the conduction of lithium ions by coating ion conductive materials, such coating can easily lead to a decrease in the electronic conductivity of the material and affect the diffusion of lithium ions and the dissipation of heat.
[0008] Therefore, there is an urgent need to design a coated high-nickel material with high surface ion / electronic conductivity, easy heat dissipation, and good compatibility with the electrolyte. Summary of the invention
[0009] The invention provides a coated high-nickel material, which has high surface ion / electronic conductivity, is easy to dissipate heat, and has good compatibility with an electrolyte.
[0010] In order to achieve the above object, the present invention provides a coated high-nickel material, comprising a high-nickel material and a coating layer coating the surface of the high-nickel material, wherein the coating layer is obtained by mixing a NASICON type fast ion conductor and a metal boride.
[0011] The present invention utilizes NASICON fast ion conductors to improve the lithium ion transmission performance and electrochemical stability between the electrode high nickel material and the electrolyte interface, while suppressing the generation of high impedance impurities to avoid a significant reduction in electronic conductivity. However, if the NASICON fast ion conductor is only wrapped, the reduction in the electronic conductivity of the battery is inevitable. Therefore, the present invention mixes metal borides in the wrapping layer to improve the electronic conductivity while ensuring the lithium ion transmission performance and electrochemical stability. Therefore, the present invention optimizes the transmission path of ions and electrons in the battery through the synergistic effect of the NASICON fast ion conductor and the metal boride, can accelerate the transmission of ions and electrons between the electrolyte and the electrode material, and helps to improve the charging and discharging efficiency and energy utilization.
[0012] The present invention can construct a heat transfer channel by mixing metal borides in the wrapping layer to transfer heat from the inside of the high-nickel material to the outside of the wrapping layer, and the NASICON type fast ion conductor can further promote the diffusion of heat through its three-dimensional mesh open structure, so that the wrapping layer has excellent thermal conductivity and accelerates the dissipation of heat.
[0013] The present invention provides a method for preventing a battery from thermal runaway at high temperatures by utilizing the high melting point and high thermal conductivity of metal borides, while the structural stability of the NASICON fast ion conductor helps maintain the normal operation of the battery under adverse conditions. Thus, the present invention achieves better thermal stability through the synergistic effect of the NASICON fast ion conductor and the metal boride.
[0014] Preferably, the weight ratio of the NASICON type fast ion conductor to the metal boride is 1:3 to 3:1.
[0015] The present invention provides an appropriate amount of NASICON type fast ion conductor and metal boride, thereby achieving an optimized balance among the electronic conductivity, ionic conductivity, thermal conductivity and electrode / electrolyte interface stability of the coated high nickel material, thereby avoiding the situation that the NASICON type fast ion conductor content is too low, which is unfavorable for the transmission of lithium ions at the interface, and excessive metal boride also hinders the effective transmission of lithium ions, resulting in a decrease in battery performance, while avoiding the situation that the metal boride content is too low, which is unfavorable for electronic transmission and heat dissipation.
[0016] Preferably, the metal boride is selected from at least one of TiB2, ZrB2, HfB2, and NbB2. The metal boride provided by the present invention has good electronic conductivity, thermal conductivity, and wear resistance. By coating with metal borides, the electronic conductivity and thermal conductivity of the material can be improved, thereby improving the rate performance and safety performance of the material. At the same time, the metal boride coating can also improve the stability of the coated high-nickel material in the air, as well as the processing performance. Compared with low-valent metal borides, the high-valent metal borides provided in this embodiment have better electronic conductivity and thermal conductivity.
[0017] If only NASICON type Li 1+x Al x Ti 2-x (PO4)3, although it can improve LiNi x Co y Mn 1-x-y The interface stability between O2 and the electrolyte improves the cycle performance of the material, but its electronic insulation is not conducive to the interfacial charge transfer reaction and the heat dissipation performance of the material; if only TiB2, ZrB2, HfB2, and NbB2 are coated, although it is beneficial to the interfacial charge transfer reaction and heat dissipation, it is not conducive to the lithium ion in LiNi x Co y Mn 1-x-y Transport at the O2 / electrolyte interface.
[0018] Further preferably, the particle size of the metal boride is 50-200 nm. The nano-scale metal boride provided in the specific embodiment of the present invention can improve the coating effect on high-nickel materials.
[0019] Preferably, the chemical formula of the NASICON type fast ion conductor is Li 1+x Al x Ti 2-x (PO4)3, wherein 0.2≤x≤0.5. The NASICON type Li 1+x Al x Ti 2-x (PO4)3 has excellent hydrophobicity, air stability, and high lithium ion conductivity, and x Co y Mn 1-x-y O2 synthesis conditions are compatible, that is, the thermodynamic synthesis conditions of the two are similar. LiNi can be stabilized by coating x Co y Mn 1-x-y O2 surface structure, inhibiting surface lattice distortion and oxygen evolution, improving the safety performance of materials and batteries, and at the same time, Li 1+x Al x Ti 2-x(PO4)3 coating can improve the performance of LiNi x Co y Mn 1-x-y The interfacial stability between O2 and electrolyte improves the cycling performance of the material. 1+x Al x Ti 2-x (PO4)3 coating can also improve the lithium ion x Co y Mn 1-x- y Interfacial transport properties between O2 and electrolyte.
[0020] Further preferably, the NASICON type Li 1+x Al x Ti 2-x The particle size of (PO4)3 is 50-200 nm. The nano-scale NASICON type Li 1+x Al x Ti 2-x (PO4)3 granular material can improve the coating effect on high-nickel materials, that is, form a uniform and continuous coating layer.
[0021] Preferably, the chemical formula of the high nickel material is LiNi x Co y Mn 1-x-y O2, wherein 0.7≤x<1, 0<y<0.2. The high nickel material provided by the present invention has a high capacity, which is beneficial to improving the energy density of the battery.
[0022] Preferably, the weight ratio of the wrapping layer to the high-nickel material is 0.2 to 2: 100. The present invention controls the content of the wrapping layer so that the surface of the high-nickel material is completely wrapped by the wrapping layer to avoid exposure of the high-nickel material, while preventing the wrapping layer from being too thick to affect heat dissipation and surface ion / electronic conductivity.
[0023] On the other hand, the present invention also provides a method for preparing the coated high-nickel material, comprising: (1) Nanoscale NASICON-type Li 1+x Al x Ti 2-x (PO4)3 and nano-sized metal borides are mixed evenly to obtain Li 1+x Al x Ti 2-x A mixture of (PO4)3 and a metal boride; (2) The mixture of step (1) is coated on the surface of high-nickel material particles by rotating the cylinder body using a mechanical fusion method to obtain the coated high-nickel material, wherein a blade is fixed on the cylinder wall of the cylinder body. During the rotation of the cylinder body, the mixture and the high-nickel material particles are tightly attached to the cylinder wall and are fully mixed under the extrusion of the fixed blade.
[0024] Preferably, the nanoscale NASICON type Li 1+x Al x Ti 2-x A method for preparing (PO4)3, comprising: Sodium dihydrogen phosphate, aluminum oxide, titanium oxide and a lithium source are weighed according to a stoichiometric ratio and ball-milled to obtain a mixture; The mixture was subjected to solid phase reaction in air atmosphere and then sand-milled to obtain Li 1+x Al x Ti 2-x (PO4)3.
[0025] More preferably, the temperature of the solid phase reaction is 850-950 o C, the reaction time is 5 to 10 hours.
[0026] Further preferably, after sand grinding, Li 1+x Al x Ti 2-x The particle size of (PO4)3 is 50 to 200 nanometers.
[0027] Preferably, the method for preparing the nano-scale metal boride comprises: crushing the metal boride by sand milling to obtain the nano-scale metal boride. The metal boride provided by the present invention is a commercially available material. Preferably, after sand milling, the particle size of the metal boride is 50 to 200 nanometers.
[0028] Preferably, in step (1), the mixing method is ball milling or high-speed mixing.
[0029] Further preferably, in step (1), the mixing method is a high-speed mixing method. By using the high-speed mixing method, the shear force during the high-speed mixing process can make the nano-NASICON type Li 1+x Al x Ti 2-x (PO4)3 and nano-sized metal borides are uniformly mixed.
[0030] On the other hand, the present invention also provides the application of the coated high-nickel material in lithium-ion batteries.
[0031] Compared with the prior art, the present invention has the following beneficial effects: The present invention utilizes a wrapping layer composed of a NASICON type fast ion conductor and a metal boride to wrap a high-nickel material to stabilize the crystal structure of the high-nickel material. The difference from the conventional method of wrapping a NASICON type fast ion conductor and a metal boride separately in layers is that the present invention mixes the NASICON type fast ion conductor and the metal boride into a layer and wraps the layer on the positive electrode material. The purpose is not only to optimize the transmission path of ions and electrons inside the battery to accelerate the transmission of ions and electrons, but also to utilize the heat transmission channel constructed by the metal boride to cooperate with the three-dimensional mesh open structure of the NASICON type fast ion conductor to promote the diffusion of heat, so that the wrapping layer has excellent thermal conductivity to accelerate the dissipation of heat.
[0032] In the application of lithium batteries prepared by the encapsulated high-nickel material of the present invention, the capacity retention rate is more than 90% after 200 charge and discharge cycles at 1 C (1 C=200 mA / g), and the material has high cycle performance. In the DSC test, the decomposition temperature of the material is above 243°C, and the material has a high decomposition temperature. Therefore, the encapsulated high-nickel material provided by the present invention has high thermal stability and safety.
[0033] The mechanical fusion method provided by the present invention can evenly wrap the mixture on the surface of the high-nickel material particles, the operation time is short, and one-piece molding can be achieved. No liquid binder is required during processing, and no drying or heating is required after processing. The uniformity and stability are excellent. After the mechanical fusion method is used, the crystal structure of the high-nickel material particles is not destroyed by mechanical fusion, and the structure and shape can be kept intact. The contour of the wrapping layer is smooth and the wrapping uniformity is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of the structure of the coated high-nickel material prepared in Example 1.
[0035] Figure 2 This is a charge and discharge curve diagram of the coated high-nickel material prepared in Example 1; Figure 3 This is a cycle performance diagram of the coated high-nickel material prepared in Example 1; Figure 4 This is the morphology of the wrapped high-nickel material prepared in Example 1. Specific embodiments
[0036] The present invention will be further described below in conjunction with the embodiments and drawings.
[0037] Although the prior art discloses using metal borides or fast ion conductors as a wrapping layer, or using fast ion conductors as the first wrapping layer close to the positive electrode material and boride as the second wrapping layer as disclosed in CN117199308A, the function of the boride disclosed therein is mainly to prevent the electrolyte from contacting the positive electrode material, and to prevent the electrolyte from reacting with the positive electrode material at high temperature to cause cracks in the positive electrode material, which is different from the function of the present application to quickly dissipate the heat generated by the positive electrode material by synergistically using boride and fast ion conductors. Therefore, the thermal stability characterization provided in the patent application is characterized by the decomposition of the electrolyte at the surface interface and the gas production, so as to illustrate the degree of reaction between the positive electrode material and the electrolyte, while the specific embodiment of the present invention uses the thermal decomposition temperature of the test material for characterization, so as to illustrate that the material provided by the specific embodiment of the present invention has a good heat dissipation effect. Therefore, although the above-mentioned comparative document discloses using boride as a coating layer, the effect produced is different. The specific embodiment of the present invention is to wrap the high nickel material by mixing NASICON fast ion conductors and metal borides to construct a wrapping layer as follows: Embodiment 1: This embodiment provides a method for preparing a coated high-nickel material, comprising: Press Li 1.3 Al 0.3 Ti 1.7 (PO4)3 stoichiometric ratio, sodium dihydrogen phosphate, aluminum oxide, titanium oxide, and lithium carbonate are used as precursors, and Li is obtained by ball milling and solid phase reaction. 1.3 Al 0.3 Ti 1.7 (PO4)3, where the solid phase reaction temperature is 900 o C, the solid phase reaction time is 7 hours.
[0038] Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and commercial NbB2 were sand-milled to obtain Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and NbB2 powders are prepared and ball milled to mix the two powders uniformly, with a weight ratio of 1:1.
[0039] The above mixture was mixed with commercial LiNi 0.8 Co 0.1 Mn 0.1 O2 is mixed uniformly by ball milling, wherein the mixture is mixed with LiNi 0.8 Co 0.1 Mn 0.1 O2 weight ratio is 0.5:100, and then Li 1.3 Al0.3 Ti 1.7 The mixed particles of (PO4)3 and NbB2 are uniformly and completely coated on LiNi 0.8 Co 0.1 Mn 0.1 O2 particle surface, the obtained coated high nickel material is recorded as A40-250109-WB2, as shown in Table 1, the powder impedance of the coated high nickel material prepared in this embodiment is two sets lower than the powder impedance of the high nickel material provided in Comparative Example 1, and the value of the powder impedance is inversely proportional to the value of the electronic conductivity, that is, the smaller the powder impedance value of the positive electrode material, the higher the electronic conductivity value of the positive electrode material. The structure of the coated material is shown in Figure 1 , the morphology is as follows Figure 4 As shown, in LiNi 0.8 Co 0.1 Mn 0.1 O2 surface coated with a layer of Li 1.3 Al 0.3 Ti 1.7 Mixed particle layer of (PO4)3 and NbB2.
[0040] The material prepared in this example was used as the positive electrode, metallic lithium was used as the negative electrode, a polypropylene film was used as the separator, and a 1 mol / L LiPF6 ethylene carbonate (EC) / diethyl carbonate (DEC) solution was used as the electrolyte. A button cell was assembled and a charge and discharge test was performed. The voltage range was 3-4.3 V. Figure 2 The discharge capacity is 191 mAh / g, and the capacity retention rate is 94% after 200 charge and discharge cycles at 1 C (1 C = 200 mA / g). Figure 3 The above-mentioned coated material was charged to 4.3 V and subjected to DSC test. The decomposition temperature of the material was 252 o C. The encapsulation layer provided in this embodiment is a layer formed by mixing a fast ion conductor and a metal boride, and mainly utilizes the combination of the heat conduction channel of the metal boride and the three-dimensional mesh open structure of the fast ion conductor to accelerate the heat dissipation and achieve thermal stability.
[0041] Embodiment 2: This embodiment provides a method for preparing a coated high-nickel material, comprising: Press Li 1.4 Al 0.4 Ti 1.6 (PO4)3 stoichiometric ratio. Sodium dihydrogen phosphate, aluminum oxide, titanium oxide, and lithium carbonate are used as precursors, and Li is obtained by ball milling and solid phase reaction. 1.4 Al 0.4 Ti 1.6 (PO4)3. The solid phase reaction temperature is 850 o C, the solid phase reaction time is 10 hours.
[0042] Li 1.4 Al 0.4 Ti 1.6 (PO4)3 and commercial TiB2 were sand-milled to obtain Li 1.4 Al 0.4 Ti 1.6 (PO4)3 and TiB2 powders are prepared and ball milled to mix the two uniformly, with a weight ratio of 3:1.
[0043] The above mixture was mixed with commercial LiNi 0.85 Co 0.05 Mn 0.10 O2 is mixed uniformly by ball milling, wherein the mixture is mixed with LiNi 0.85 Co 0.05 Mn 0.10 O2 weight ratio is 1:100, and then coated by mechanical fusion method to 1.4 Al 0.4 Ti 1.6 The mixed particles of (PO4)3 and TiB2 are uniformly and completely coated on LiNi 0.85 Co 0.05 Mn 0.10 O2 particle surface.
[0044] Electrochemical tests were performed according to the method of Example 1. The capacity retention rate was 90.8% after 200 cycles of 1 C charge and discharge. The above-mentioned coated material was charged to 4.3 V and subjected to DSC test. The decomposition temperature was 243 o C.
[0045] Comparative Example 1: Materials were prepared according to the method of Example 1, except that: LiNi 0.8 Co 0.1 Mn 0.1 The O2 material was not coated in any way, and the obtained high-nickel material was recorded as A40-250109-WB1.
[0046] The rest is the same as Example 1 and will not be described again here.
[0047] Electrochemical tests were carried out according to the method of Example 1. The capacity retention rate was 75.8% after 200 cycles of 1 C charge and discharge. The above material was charged to 4.3 V and the decomposition temperature was 227 o C.
[0048] Table 1 shows the powder impedance of high nickel materials obtained in Example 1 and Comparative Example 1
[0049]
[0050] Comparative Example 2: Materials were prepared according to the method of Example 1, except that: LiNi 0.8 Co 0.1 Mn 0.1 O2 material only coats Li 1.3 Al 0.3 Ti 1.7 (PO4)3, not coated with NbB2.
[0051] The rest is the same as Example 1 and will not be described again here.
[0052] Electrochemical tests were carried out according to the method of Example 1. After 200 cycles of 1 C charge and discharge, the capacity retention rate was 83.6%. The above material was charged to 4.3 V and tested by DSC. The decomposition temperature was 231 o C.
[0053] Comparative Example 3: Materials were prepared according to the method of Example 1, except that: LiNi 0.8 Co 0.1 Mn 0.1 The O2 material only coats NbB2 but not Li 1.3 Al 0.3 Ti 1.7 (PO4)3.
[0054] The rest is the same as Example 1 and will not be described again here.
[0055] Electrochemical tests were carried out according to the method of Example 1. The capacity retention rate was 84.6% after 200 cycles of 1 C charge and discharge. The above material was charged to 4.3 V and the decomposition temperature was 236 o C.
[0056] Comparative Example 4: The material is prepared according to the method of Example 1, except that NbB2 is replaced with an equal weight of Nb2O5.
[0057] The rest is the same as Example 1 and will not be described again here.
[0058] Electrochemical tests were carried out according to the method of Example 1. The capacity retention rate was 83.9% after 200 cycles of 1 C charge and discharge. The above material was charged to 4.3 V and the decomposition temperature was 232 o C.
Claims
1. A coated high-nickel material, characterized in that: The invention comprises a high-nickel material and a wrapping layer for wrapping the surface of the high-nickel material, wherein the wrapping layer is obtained by mixing a NASICON type fast ion conductor and a metal boride.
2. The coated high-nickel material according to claim 1, characterized in that: The weight ratio of the NASICON type fast ion conductor to the metal boride is 1:3 to 3:
1.
3. The coated high-nickel material according to claim 2, characterized in that: The metal boride is selected from at least one of TiB2, ZrB2, HfB2, and NbB2.
4. The coated high-nickel material according to claim 3, characterized in that: The particle size of the metal boride is 50-200 nm.
5. The coated high-nickel material according to claim 1 or 3, characterized in that: The chemical formula of the NASICON type fast ion conductor is Li 1+x Al x Ti 2-x (PO4)3, where 0.2≤x≤0.
5.
6. The coated high-nickel material according to claim 5, characterized in that: The NASICON type Li 1+x Al x Ti 2-x The particle size of (PO4)3 is 50-200 nm.
7. The coated high-nickel material according to claim 1, characterized in that: The weight ratio of the wrapping layer to the high-nickel material is 0.2 to 2:
100.
8. The coated high-nickel material according to claim 1, characterized in that: The general chemical formula of the high nickel material is LiNi x Co y Mn 1-x-y O2, where 0.7≤x<1, 0<y<0.
2.
9. A method for preparing a coated high-nickel material according to any one of claims 1 to 8, characterized in that: include: (1) Nanoscale NASICON-type Li 1+x Al x Ti 2-x (PO4)3 and nano-sized metal borides are mixed evenly to obtain Li 1+ x Al x Ti 2-x A mixture of (PO4)3 and a metal boride; (2) The mixture of step (1) is coated on the surface of high-nickel material particles by rotating the cylinder body using a mechanical fusion method to obtain the coated high-nickel material, wherein a blade is fixed on the cylinder wall of the cylinder body. During the rotation of the cylinder body, the mixture and the high-nickel material particles are tightly attached to the cylinder wall and are fully mixed under the extrusion of the fixed blade.
10. Use of the coated high-nickel material according to any one of claims 1 to 8 in a lithium-ion battery.
Citation Information
Patent Citations
Coated modified high-nickel ternary positive electrode material as well as preparation method and application thereof
CN115425214A
NASICON type solid electrolyte, positive electrode material and preparation method and application of NASICON type solid electrolyte and positive electrode material
CN116799291A
Double-coating-layer positive electrode material, preparation method thereof and lithium ion battery
CN117199308A
High-nickel ternary electrode material and preparation method thereof
CN107689450A
LATP / high-nickel composite positive electrode material, positive plate and battery
CN114551819A